Mangrove environmental services, participation, and ecotourism: mapping global research trends through bibliometric analysis. - Adisan; Ikhwan; Didin Pratama; Furkan (Journal of Biology, Environment, and Edu-Tourism, 2025)
Challenges in mangrove ecosystem management arise from the polarization of values between local economic benefits (livelihoods) and global ecological concepts (Blue Carbon), as well as the critical issue of community participation. Through a bibliometric analysis of 300 documents (2021–2025) from the Scopus/Web of Science database, this study aims to map research trends and identify literature gaps related to mangrove ecosystem services, community participation, and ecotourism. Network analysis reveals a strong centrality to livelihoods, reflecting a research focus that is predominantly driven by economic benefits. In contrast, Blue Carbon is situated on the periphery of the network, highlighting the research focus gap. Recent research trends are shifting toward regulation and institutions (governance). This study’s scientific contribution is to offer research priorities to bridge this value gap by internalizing ecological concepts into local practices as a fundamental strategy for enhancing sustainable participation and synchronizing local conservation with the global climate agenda.